2022
DOI: 10.1097/rti.0000000000000647
|View full text |Cite
|
Sign up to set email alerts
|

A Challenge for Emphysema Quantification Using a Deep Learning Algorithm With Low-dose Chest Computed Tomography

Abstract: Purpose: We aimed to identify clinically relevant deep learning algorithms for emphysema quantification using low-dose chest computed tomography (LDCT) through an invitation-based competition. Materials and Methods: The Korean Society of Imaging Informatics in Medicine (KSIIM) organized a challenge for emphysema quantification between November 24, 2020 and January 26, 2021. Seven invited research teams participated in this challenge. In total, 558 pairs of computed tomography (CT) scans (468 pairs for the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Iterative reconstruction techniques synthesize projections by modelling the data collection process based on the noise properties of the imaged objects to allow dose reductions of 32~65% without increasing noise in the reconstructed images that are produced. Recently, one study evaluated the performance of various deep learning-based algorithms for emphysema quantification using a dataset with different low dose CT protocols and showed that intraclass correlation coefficients of emphysema index between standard-dose CT and converted low-dose CT scans using deep learning-based algorithms ranged from 0.85 to 0.94 [ 22 ]. Although deep learning-based algorithms can improve emphysema quantification from low-dose CT with heterogenous CT protocols, it is not clear whether this also applies to emphysema quantification for ultra-low-dose CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…Iterative reconstruction techniques synthesize projections by modelling the data collection process based on the noise properties of the imaged objects to allow dose reductions of 32~65% without increasing noise in the reconstructed images that are produced. Recently, one study evaluated the performance of various deep learning-based algorithms for emphysema quantification using a dataset with different low dose CT protocols and showed that intraclass correlation coefficients of emphysema index between standard-dose CT and converted low-dose CT scans using deep learning-based algorithms ranged from 0.85 to 0.94 [ 22 ]. Although deep learning-based algorithms can improve emphysema quantification from low-dose CT with heterogenous CT protocols, it is not clear whether this also applies to emphysema quantification for ultra-low-dose CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…2, 3). The algorithm was based on a 2.5-dimensional U-net architecture and was trained with 468 pairs of LDCT and standard-dose CT images obtained from patients at 9 different institutions using various scanners 20 . The detailed information regarding the development of the kernel adaptation algorithm is described in a previous literature 20 .…”
Section: Methodsmentioning
confidence: 99%
“…Reduction of noise in CT images obtained using lower radiation dose is a representative application of these artificial intelligence algorithms 16–18 . Generation of images mimicking standard-dose, low-frequency kernel CT images from low-dose, high-frequency kernel CT images may help in better quantitative evaluation of pulmonary emphysema and prediction of long-term outcomes of individuals undergoing LDCTs 19,20 …”
mentioning
confidence: 99%
“…Pulmonary emphysema is de ned as abnormal permanent enlargement of airspaces distal to the terminal bronchioles [8,9] and results in low attenuated areas (LAA) in chest CT which are below -950 Hounse eld unit (HU). [3] Since the extent of emphysema in CT is associated with pulmonary function decline, [10] variables representing emphysema were evaluated.…”
Section: Variables Explanation and Outcome De Nitionmentioning
confidence: 99%